2013
DOI: 10.4021/jocmr1256w
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Reduced Efficacy of Sitagliptin Therapy: Analysis of 93 Patients With Type 2 Diabetes Treated for 1.5 Years or Longer

Abstract: BackgroundSeveral studies have shown the effectiveness of sitagliptin, a dipeptidyl peptidase-4 inhibitor, for type 2 diabetes, with a hypoglycemic effect being demonstrated both when it is administered alone or in combination with other oral antidiabetic agents. However, there are few reports about its long-term efficacy, although medications for diabetes need to be effective over the long term. This study (as part of ASSET-K) aimed to investigate the efficacy and safety of sitagliptin when it was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 23 publications
1
29
2
Order By: Relevance
“…The present study showed that Δbody weight and duration of diabetes were the contributing factors for the maintenance of long-term response, specifically ΔHbA1c (24-3 months) in the completed group. This is why, in contrast to the study of Hamaguchi et al, short-term response alone could not be used to predict the long-term response in the present study compared to the study of Hamaguchi et al Kanamori et al reported similar results to the present study when they found that inadequate compliance with diet and exercise therapy causes weight gain and that increased body weight is associated with the reduced efficacy of sitagliptin therapy (21). Meanwhile, Kubota et al reported that body weight gain between 24 and 52 weeks influences the persistence of the glucose-lowering effect of sitagliptin combined with a sulfonylurea during 1 year of follow-up (22).…”
Section: Discussioncontrasting
confidence: 89%
“…The present study showed that Δbody weight and duration of diabetes were the contributing factors for the maintenance of long-term response, specifically ΔHbA1c (24-3 months) in the completed group. This is why, in contrast to the study of Hamaguchi et al, short-term response alone could not be used to predict the long-term response in the present study compared to the study of Hamaguchi et al Kanamori et al reported similar results to the present study when they found that inadequate compliance with diet and exercise therapy causes weight gain and that increased body weight is associated with the reduced efficacy of sitagliptin therapy (21). Meanwhile, Kubota et al reported that body weight gain between 24 and 52 weeks influences the persistence of the glucose-lowering effect of sitagliptin combined with a sulfonylurea during 1 year of follow-up (22).…”
Section: Discussioncontrasting
confidence: 89%
“…Considering these concepts, SGLT2 inhibitors may be a useful addition to the treatment regimen in patients with higher BMI who respond poorly to a DPP‐4 inhibitor. It has also been reported that body weight management is important for maintaining good long‐term glycaemic control with DPP‐4 inhibitors . In the present study, the reductions in HbA1c and body weight were maintained for 52 weeks without attenuation, and 82.24% of patients showed decreases in both HbA1c and body weight at the end of the treatment period.…”
Section: Discussionsupporting
confidence: 60%
“…It has also been reported that body weight management is important for maintaining good longterm glycaemic control with DPP-4 inhibitors. 36,37 In the present study, the reductions in HbA1c and body weight were maintained for 52 weeks without attenuation, and 82.24% of patients showed decreases in both HbA1c and body weight at the end of the treatment period.…”
Section: Discussionmentioning
confidence: 48%
“…These factors, including dietary habits, exercise, lifestyle, body weight alterations, the insulin secretion capacity and insulin resistance. In addition, the previous report indicated that sitagliptin treatment efficacy was attenuated during the 12-month study period (26). These ideas might have affected the result.…”
Section: Discussionmentioning
confidence: 93%